1997
DOI: 10.1128/jvi.71.8.6208-6213.1997
|View full text |Cite
|
Sign up to set email alerts
|

Probing the substrate specificity of hepatitis C virus NS3 serine protease by using synthetic peptides

Abstract: We probed the substrate specificity of a recombinant noncovalent complex of the full-length hepatitis C virus (HCV) NS3 serine protease and NS4A cofactor, using a series of small synthetic peptides derived from the three trans-cleavage sites of the HCV nonstructural protein sequence. We observed a distinct cleavage site preference exhibited by the enzyme complex. The values of the turnover number (k cat) for the most efficient NS4A/4B, 4B/5A, and 5A/5B peptide substrates were 1.6, 11, and 8 min ؊1 , respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 48 publications
3
63
1
Order By: Relevance
“…The substrate specificity determined in this way was later confirmed using synthetic peptides spanning the scissile bonds. It was found that the NS3/4A proteinase required at least decamer peptides from the P6-P4' position, although longer peptides appeared to be cleaved with higher efficiency [97,115]. The enzyme has a preference for substrates with an acidic residue in P6, a cysteine in P1 and serine or alanine in P1' [105,115,116] (Fig.…”
Section: Substrate Specificity Of the Ns3/4a Proteinasementioning
confidence: 99%
“…The substrate specificity determined in this way was later confirmed using synthetic peptides spanning the scissile bonds. It was found that the NS3/4A proteinase required at least decamer peptides from the P6-P4' position, although longer peptides appeared to be cleaved with higher efficiency [97,115]. The enzyme has a preference for substrates with an acidic residue in P6, a cysteine in P1 and serine or alanine in P1' [105,115,116] (Fig.…”
Section: Substrate Specificity Of the Ns3/4a Proteinasementioning
confidence: 99%
“…The cytotoxicity of DTA and RTA based zymoxins is elevated in a hepatoma-derived cell line stably expressing NS3 protease or infected with HCV In order to evaluate the potential of the described zymoxins to be cleaved in the cytoplasm of HCV infected cells, Huh7.5 hepatoma cells uninfected or infected with the 1a/2a chimeric virus HJ3-5 (encoding the structural proteins of genotype 1a strain H77S within the background of genotype 2a strain JFH1) [55,56] were transfected with a new set of cleavage substrates encoding vectors. These vectors, named ''pCMV/MBP-EGFP-full 1b NS5AB-CBD'' and ''pCMV/MBP-EGFP-full 2a JFH1 NS5AB-CBD'', encodes for the previously described NS3 cleavable substrate, with the following modifications: the 10 amino acid minimal NS3 cleavage sequence from genotype 1b/1a NS5A/B junction was replaced by longer cleavage sequences of 18 amino acids (P10-P89) and 20 amino-acids (P10-P109) from 1b or 2a (strain JFH1) genotype NS5A/B junction sites, respectively ( longer recognition sequences were demonstrated to be cleaved more efficiently by NS3 [57]). Western blot analysis of lysate samples from uninfected and HJ3-5 infected cells indicates the cleavage of the substrate incorporating the 2a NS5A/B site in infected cells (in which the NS3 protease encoded by the 2a genotype component of the chimera is expressed) (Fig.…”
Section: The Cytotoxicity Of Rta-based Zymoxin Is Elevated In Ns3 Expmentioning
confidence: 99%
“…Comparison of the NS3/4A protease cleavage sites shows only three positions that are conserved: E/DXXXXC/T-S/A (Bartenschlager 1999). The availability of a robust recombinant enzyme assay revealed that the enzyme recognizes a ten amino acid stretch of the substrate, from P6 to P4 (Steinkuhler et al 1996;Zhang et al 1997), with the P1 Cys being the major determinant of cleavage site recognition (Bartenschlager 1999). The structures confirmed earlier modeling studies that placed a Phe residue at the bottom of the S1 subsite in position to allow van der Fig.…”
Section: Discovery and Structure Of The Hcv Ns3/4a Serine Proteasementioning
confidence: 99%